Drug-Induced Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis: A Retrospective Study on Causative Agents and Patient Profiles in an Indonesian Hospital Setting - Nurrachmat Mulianto; Lidjaja, Lifesia Natali (HM Publisher, 2025)
Background: Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) represent rare, severe mucocutaneous adverse drug reactions characterized by extensive epidermal necrosis and significant morbidity and mortality. Understanding the specific causative agents and patient profiles within local populations is crucial for early diagnosis and management. This study aimed to characterize SJS/TEN cases in a tertiary hospital setting in Indonesia. Methods: A retrospective descriptive study was conducted using secondary data from medical records of patients diagnosed with SJS, SJS/TEN overlap, and TEN admitted to the inpatient installation of Dr. Moewardi General Hospital, Surakarta, Indonesia, between January 2022 and December 2024. Data collected included demographics (age, gender), comorbidities, diagnosis classification (SJS, SJS/TEN overlap, TEN), suspected causative drugs, length of hospital stay, SCORTEN score, and patient outcome (discharged alive or deceased). Total sampling was employed, excluding records with incomplete data. Data were compiled and analyzed descriptively. Results: Fifty-one patients were included, with a slight female predominance (52.94%). The largest age group affected was 19-59 years (60.78%). The distribution of diagnoses was SJS (41.18%), SJS/TEN overlap (31.37%), and TEN (27.45%). The mean SCORTEN score for the cohort was 2. The most common suspected causative drug classes were antibiotics (25.71%), followed by analgesic-antipyretics (24.29%), and anticonvulsants (22.86%). Carbamazepine (11.43%) and amoxicillin (10%) were frequent individual culprits. Epilepsy (13.73%) and diabetes mellitus (11.76%) were common comorbidities, although a significant portion (33.33%) had no recorded comorbidity. The mean length of stay was 9 days. Overall mortality was 15.68%, with higher rates observed in TEN (28.57%) compared to SJS (9.52%) and SJS/TEN overlap (12.5%). Conclusion: SJS/TEN affected predominantly adults, with antibiotics, analgesics, and anticonvulsants being the most implicated drug classes. While mortality was considerable, it appeared lower than some international reports, particularly for TEN. Recognizing common causative agents and patient risk factors, such as specific comorbidities like epilepsy and diabetes, can aid clinicians in early identification and prompt management of these life-threatening conditions.